2016
DOI: 10.1177/0009922815623498
|View full text |Cite
|
Sign up to set email alerts
|

Social Risk Screening for Pediatric Inpatients

Abstract: This systematic review aims to identify existing social risk screening instruments applicable to hospitalized children (primary) and evaluate their content validity and methodological quality (secondary). Individual questions were abstracted and sorted by social risk theme. Content validity was evaluated by 13 hospital-based social workers. Methodological quality was assessed using the 108-item Consensus Based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist. A total of 1070 cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In summary, similar to prior systematic reviews of social risk screening tools for use in pediatric settings (Pai et al, 2016), this review found that the majority of tools focused on only a limited number of SDOH domains and lacked exploration of the individual components within each domain. There was significant heterogeneity among methods used to assess SDOH risks, and existing tools lacked content validation and consistency among SDOH domains assessed.…”
Section: Synthesis Of the Literaturesupporting
confidence: 57%
See 2 more Smart Citations
“…In summary, similar to prior systematic reviews of social risk screening tools for use in pediatric settings (Pai et al, 2016), this review found that the majority of tools focused on only a limited number of SDOH domains and lacked exploration of the individual components within each domain. There was significant heterogeneity among methods used to assess SDOH risks, and existing tools lacked content validation and consistency among SDOH domains assessed.…”
Section: Synthesis Of the Literaturesupporting
confidence: 57%
“…Clinician barriers such as time constraints, having inadequate risk assessment training and a lack of knowledge of available community resources for addressing SDOH (Beck, Klein & Kahn, 2012), in addition to concern or discomfort discussing sensitive topics such as income or domestic violence with patients and families (Beaune et al, 2014; Beck et al, 2012) have been reported. Other barriers to screening include the belief that assessing SDOH is outside the purview of clinical medical care (DeJong et al, 2016), or that it is a task that is better handled by trained social work teams (Pai et al, 2016). Finally, clinicians may also have the perception that SDOH are not remediable and therefore, assessment serves no purpose (Klein et al, 2013).…”
Section: Clinical Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, database searches were supplemented with hand searches for particular tools identified by content experts, references of relevant systematic reviews, 4,16,23 and a list of screening tools published by the Social Interventions Research and Evaluation Network. 31 To identify relevant uses of included screening tools in clinical practice, Google Scholar cited-by searches for each included tool were also used.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…11,12 In addition, screening tools with favorable pragmatic properties (e.g., brief, easy to administer and score, and free or low cost) may promote implementation and translation of research into practice, 13,14 but developers traditionally have not approached the tool development process with both psychometric and pragmatic considerations in mind. 15 However, despite the rapid proliferation and implementation of social risk screening tools, 16,17 neither the psychometric nor pragmatic measurement qualities of these tools is well understood.…”
mentioning
confidence: 99%